Availability and readiness of health facilities for non-communicable disease services in Ethiopia: Evidence from the nationally representative health facility survey 2022 - Andualem Yalew Aschalew; Jenberu Mekurianew Kelkay; Getachew Teshale; Kaleb Assegid Demissie; Nebebe Demis Baykemagn; Azmeraw Tadele; Misganaw Guadie Tiruneh; Tesfahun Zemene Tafere; Asebe Hagos; Melak Jejaw (PLoS ONE, 2025)
Background In response to the escalating non-communicable disease (NCD) challenge, effective management of NCDs requires sustained investments in infrastructure, trained health workforce, and the consistent availability of guidelines. Therefore, this study assessed both the availability and readiness of health facilities (HFs) to provide NCD-related services, while also examining how facility characteristics and health system factors are associated with service readiness. Methods We analysed data from the nationally representative Ethiopia Service Provision Assessment (ESPA) survey 2021−22 to determine the availability and readiness of HFs for cardiovascular diseases (CVDs), diabetes, chronic respiratory diseases (CRDs) and mental, neurological and substance (MNS) use disorders-related services using the WHO Service Availability and Readiness Assessment manual. Readiness score was measured as the average availability of tracer items in percent, and HFs were considered ‘ready’ for NCDs management if they scored ≥70 (out of 100). We performed weighted multivariable logistic regression to identify factors affecting NCD service readiness. Results Approximately 93% reported offering services for diabetes, CVDs, and CRDs, while only 26% provided MH services. Overall service readiness remains critically low when applying the 70% readiness threshold. Only 15.68% of facilities were deemed ready for diabetes, 10.64% for CVDs, 3.14% for CRDs, and 11.52% for MNS use disorders-related services. Public facilities demonstrated significantly higher preparedness than private facilities. A number of factors have been associated with better service readiness, including the location of the facility, the level of the facility, having a quality control unit, conducting regular administrative meetings and receiving external supervision. Conclusions This study reveals that overall service readiness for NCDs remains significantly low across HFs in Ethiopia. Public facilities and facilities located in urban settings demonstrated significantly higher levels of service readiness, highlighting substantial disparities in resource availability, integration with national health programs, and access to support systems. These findings underscore the need for Ethiopia’s health system to move beyond service availability and focus on enhancing the preparedness of care delivery, with particular emphasis on equity and integration.